Haemodynamic Monitoring in the Intensive Care Unit: Results from a Web-Based Swiss Survey. (22nd April 2014) - Siegenthaler, Nils; Giraud, Raphael; Saxer, Till; Courvoisier, Delphine S.; Romand, Jacques-André; Bendjelid, Karim
Abstract : Background . The aim of this survey was to describe, in a situation of growing availability of monitoring devices and parameters, the practices in haemodynamic monitoring at the bedside. Methods . We conducted a Web-based survey in Swiss adult ICUs (2009-2010). The questionnaire explored the kind of monitoring used and how the fluid management was addressed. Results . Our survey included 71% of Swiss ICUs. Echocardiography (95%), pulmonary artery catheter (PAC: 85%), and transpulmonary thermodilution (TPTD) (82%) were the most commonly used. TPTD and PAC were frequently both available, although TPTD was the preferred technique. Echocardiography was widely available (95%) but seems to be rarely performed by intensivists themselves. Guidelines for the management of fluid infusion were available in 45% of ICUs. For the prediction of fluid responsiveness, intensivists rely preferentially on dynamic indices or echocardiographic parameters, but static parameters, such as central venous pressure or pulmonary artery occlusion pressure, were still used. Conclusions . In most Swiss ICUs, multiple haemodynamic monitoring devices are available, although TPTD is most commonly used. Despite the usefulness of echocardiography and its large availability, it is not widely performed by Swiss intensivists themselves. Regarding fluid management, several parameters are used without a clear consensus for the optimal method.